2011
DOI: 10.1177/0300985811415708
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hydrocephalus in Genetically Engineered Mice

Abstract: There is evidence that genetic factors play a role in the complex multifactorial pathogenesis of hydrocephalus. Identification of the genes involved in the development of this neurologic disorder in animal models may elucidate factors responsible for the excessive accumulation of cerebrospinal fluid in hydrocephalic humans. The authors report here a brief summary of findings from 12 lines of genetically engineered mice that presented with autosomal recessive congenital hydrocephalus. This study illustrates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
155
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(164 citation statements)
references
References 110 publications
7
155
0
2
Order By: Relevance
“…25 Remarkably, mutations of Celsr2, Fzd3, Ulk4 and Stk36 are all found as risk factors of congenital hydrocephalus. 27 We show that Ulk4 deficiency impairs cilia formation and function, leading to hydrocephalus. This may be mediated by dysregulated Foxj1 and Wnt signaling.…”
mentioning
confidence: 77%
“…25 Remarkably, mutations of Celsr2, Fzd3, Ulk4 and Stk36 are all found as risk factors of congenital hydrocephalus. 27 We show that Ulk4 deficiency impairs cilia formation and function, leading to hydrocephalus. This may be mediated by dysregulated Foxj1 and Wnt signaling.…”
mentioning
confidence: 77%
“…Recent GWAS studies suggest it is a risk locus for multiple myeloma (Broderick et al, 2011) and interindividual diastolic blood pressure variation (Levy et al, 2009). Null mice with targeted deletion of Ulk4 were recently reported to develop congenital hydrocephalus, and their respiratory epithelia and ependymal cells had shorter cilia than normal, indicating ciliopathies (Vogel et al, 2012). Intriguingly, many imaging studies have suggested that schizophrenia patients have increased global or regional cerebrospinal fluid (Ananth et al, 2002;Bose et al, 2009;Hulshoff Pol et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Early pattern formation genes such as SHH, ZIC2, PAX6, and WNT1, neuronal path-finding genes such as L1CAM, genes related to cortical development such as POMT1, and those related to growth regulation such as PIK3CA and AKT3 have been implicated. 1,3,7,10,29,52,53,72,84,85,91,103,122 Developmental disorders presenting with hydrocephalus include neural tube disorders, forebrain and hindbrain developmental disorders, brain growth disorders, and cortical malformations. Alterations in the choroid plexus, ependyma, aqueduct, ventricles, and extraaxial spaces can also lead to hydrocephalus.…”
Section: Theme 1: Causes Of Hydrocephalus Geneticsmentioning
confidence: 99%